Anaerobic fermentation treatment improved Cd2+ adsorption of different feedstocks based hydrochars. (January 2021) - Fu, Haibin; Wang, Bingyu; Li, Detian; Xue, Lihong; Hua, Yun; Feng, Yanfang; Xie, Huifang
Abstract: Hydrothermal carbonization technology has attracted wide attention in recent years owing to its advantages, e.g., high yield and clean production, compared with traditional pyrolysis. Anaerobic fermentation (AF) is a new method to modify carbon materials, which may improve the surface properties of hydrochar (HC). To explore whether AF has effects on different feedstocks based HCs, two kinds of HCs derived from wheat straw and poplar sawdust were treated with AF for different time in this study. By comparing the changes in physicochemical properties of anaerobic fermentative hydrochars (AFHCs), adsorption behaviors of Cadmium (Cd 2+ ) on AFHCs were evaluated. The results showed that the surface electrical characteristics, specific surface area, and oxygen-containing functional groups of HCs improved significantly after AF treatment, which confirmed our hypothesis that AF is suitable for improving the adsorption of different feedstocks based HCs. The adsorption capacity of Cd 2+ on AFHCs was significantly enhanced by a 3.1–3.4 times increase after AF treatment. The effect of AF treatment on wheat straw hydrochar (WHC) was more evident than poplar sawdust hydrochar (SHC). WHCs treated with AF own higher adsorption capacity of Cd 2+, which was attributed to the higher negative charge, more exchangeable cations, and more oxygen-containing functional groups. The adsorption process was found to be a spontaneous endothermic reaction dominated by chemisorption and controlled by electrostatic attraction, ion exchange, functional groups complexation, and π-bonding coordination. These results were contributed to understanding the modification of HC by AF and its application in heavy metal pollution remediation. Graphical abstract: Image 1 Highlights: Straw hydrochar and sawdust hydrochar were produced by hydrothermal carbonization. Two different hydrochars were modified by anaerobic fermentation (AF) process. Specific surface area and more oxygen functional groups increased after AF treatment. Adsorption capacity of Cd 2+ on both hydrochars enhanced after AF treatment. AF treatment obviously improved the Cd 2+ adsorption on straw hydrochar.